Une première expérience d'écriture collaborative – Enjeux et défis de co-création des textes selon la perspective des membres d'un groupe nouvellement constitué - Krzysztof Kotuła (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This article focuses on the issue of collaborative writing in Web 2.0 era. The present study is the result of a research conducted by the author among 36 Polish secondary school students learning French. The participants were randomly assigned to 12 groups comprising three learners each. Their task consisted in writing a story based on the video game Bermuda Escape over a five-week period. One of the study's goals was to determine how L2 students engage in the collaborative writing process using Web-based word processing tools. We also wanted to determine the nature of group participation in Web-based collaborative writing as well as indicate what factors can influence students' perception of collaborative writing tasks.